Synthesis of (Z)-3-[amino(phenyl)methylidene]-1,3-dihydro-2H-indol-2-ones using an Eschenmoser coupling reaction - Marek, Lukáš; Kolman, Lukáš; Váňa, Jiří; Svoboda, Jan; Hanusek, Jiří (Beilstein Journal of Organic Chemistry, 2021)
A highly modular method for the synthesis of (Z)-3-[amino(phenyl/methyl)methylidene]-1,3-dihydro-2H-indol-2-ones starting from easily available 3-bromooxindoles or (2-oxoindolin-3-yl)triflate and thioacetamides or thiobenzamides is described. A series of 49 compounds, several of which have previously been shown to possess significant tyrosin kinase inhibiting activity, was prepared in yields varying mostly from 70 to 97% and always surpassing those obtained by other published methods. The method includes an Eschenmoser coupling reaction, which is very feasible (even without using a thiophile except tertiary amides) and scalable. The (Z)-configuration of all products was confirmed by NMR techniques.
Keywords: 3-bromooxindoles; Eschenmoser coupling reaction; thioamides; tyrosin kinase inhibitors; (Z)-3-[amino(phenyl)methylidene]-1,3-dihydro-2H-indol-2-ones

U.S. Patent - Howard, H. R., Jr; Sarges, R. (Heteroylidene indolone compounds, 1984)

(untitled) - Sarges, R.; Howard, H. R.; Koe, B. K.; Weissman, A. (J. Med. Chem., 1989)

WO Pat. Appl. - Davis, S. T.; Dickerson, S. H.; Frye, S. V.; Harris, P. A.; Hunter, R. N.; Kuyper, L. F.; Lackney, K. E.; Lackney, M. J.; Veal, J. M.; Walker, D. H. (Substituted oxindole derivatives as protein tyrosine kinase and as protein serine/threonine kinase inhibitors, 1999)

U.S. Pat. Appl. - Grell, W.; Wittneben, H.; van Meel, J. C. A.; Redemann, N.; Walter, R.; Himmelsbach, F.; Haigh, R. (Indolinones having kinase-inhibiting activity, 2000)

(untitled) - Bramson, H. N.; Corona, J.; Davis, S. T.; Dickerson, S. H.; Edelstein, M.; Frye, S. V.; Gampe, R. T.; Harris, P. A.; Hassell, A.; Holmes, W. D.; Hunter, R. N.; Lackey, K. E.; et al. (J. Med. Chem., 2001)

U.S. Pat. Appl. - Andrews, S. W.; Wurster, J. A.; Wang, E. H.; Malone, T. (3-(Arylamino)methylene-1,3-dihydro-2H-ondol-2-ones as kinase inhibitors, 2003)

(untitled) - Hauf, S.; Cole, R. W.; LaTerra, S.; Zimmer, C.; Schnapp, G.; Walter, R.; Heckel, A.; van Meel, J.; Rieder, C. L.; Peters, J.-M. (J. Cell Biol., 2003)

(untitled) - Wood, E. R.; Kuyper, L.; Petrov, K. G.; Hunter, R. N., III; Harris, P. A.; Lackey, K. (Bioorg. Med. Chem. Lett., 2004)

(untitled) - Bouchikhi, F.; Rossignol, E.; Sancelme, M.; Aboab, B.; Anizon, F.; Fabbro, D.; Prudhomme, M.; Moreau, P. (Eur. J. Med. Chem., 2008)

(untitled) - Jetton, N.; Rothberg, K. G.; Hubbard, J. G.; Wise, J.; Li, Y.; Ball, H. L.; Ruben, L. (Mol. Microbiol., 2009)

WO Pat. Appl. - Burgdorf, L. T.; Bruge, D.; Greiner, H.; Kordowicz, M.; Sirrenberg, C.; Zenke, F. (Oxindoles as kinase inhibitors, 2006)

(untitled) - Roth, G. J.; Heckel, A.; Colbatzky, F.; Handschuh, S.; Kley, J.; Lehmann-Lintz, T.; Lotz, R.; Tontsch-Grunt, U.; Walter, R.; Hilberg, F. (J. Med. Chem., 2009)

Successful Drug Discovery - Roth, G. J.; Binder, R.; Colbatzky, F.; Dallinger, C.; Schlenker-Herceg, R.; Hilberg, F.; Wollin, L.; Park, J.; Pautsch, A.; Kaiser, R. (Discovery and Development of Nintedanib: A Novel Antiangiogenic and Antifibrotic Agent, 2017)

(untitled) - Bisht, G. S.; Gnanaprakasam, B. (J. Org. Chem., 2019)

(untitled) - Wenkert, E.; Udelhofen, J. H.; Bhattacharyya, N. K. (J. Am. Chem. Soc., 1959)

(untitled) - Erba, E.; Pocar, D.; Valle, M. (J. Chem. Soc., Perkin Trans. 1, 1999)

(untitled) - Pedras, M. S. C.; Sorensen, J. L.; Okanga, F. I.; Zaharia, I. L. (Bioorg. Med. Chem. Lett., 1999)

(untitled) - Behringer, H.; Weissauer, H. (Chem. Ber., 1952)

(untitled) - Wolfbeis, O. S. (Monatsh. Chem., 1981)

U.S. Pat. Appl. - Heckel, A.; Roth, J.; Kley, S.; Hoerer, S.; Uphues, I. (Alkyl-containing 5-acylindolinones, the preparation thereof and their use as medicaments, 2005)

(untitled) - Tang, S.; Yu, Q.-F.; Peng; Li, J.-H.; Zhong, P.; Tang, R.-Y. (Org. Lett., 2007)

(untitled) - Miura, T.; Toyoshima, T.; Takahashi, Y.; Murakami, M. (Org. Lett., 2009)

(untitled) - Cantagrel, G.; de Carné-Carnavalet, B.; Meyer, C.; Cossy, J. (Org. Lett., 2009)

(untitled) - Tang, S.; Peng; Pi, S.-F.; Liang, Y.; Wang, N.-X.; Li, J.-H. (Org. Lett., 2008)

(untitled) - Tang, S.; Peng, P.; Wang, Z.-Q.; Tang, B.-X.; Deng, C.-L.; Li, J.-H.; Zhong, P.; Wang, N.-X. (Org. Lett., 2008)

(untitled) - Peng, P.; Tang, B.-X.; Pi, S.-F.; Liang, Y.; Li, J.-H. (J. Org. Chem., 2009)

(untitled) - Jiang, H.; Feng, Z.; Chen, T.; Li, Z.; Huang, W.; Luo, Y.; Zhao, Y. (J. Chem. Res., 2018)

(untitled) - Otomasu, H.; Yoshida, K.; Natori, K. (Chem. Pharm. Bull., 1975)

(untitled) - Aurich, H. G. (Justus Liebigs Ann. Chem., 1970)

(untitled) - Reisch, J.; Ossenkop, W. F. (Chem. Ber., 1973)

(untitled) - Stauss, U.; Härter, H. P.; Neuenschwander, M.; Schindler, O. (Helv. Chim. Acta, 1972)

(untitled) - Kammel, R.; Tarabová, D.; Růžičková, Z.; Hanusek, J. (Tetrahedron Lett., 2015)

(untitled) - Kammel, R.; Tarabová, D.; Brož, B.; Hladíková, V.; Hanusek, J. (Tetrahedron, 2017)

Acids and Bases. Solvent Effects on Acid-Base Strength - Cox, B. G. (Oxford University Press, 2013)

(untitled) - Hansch, C.; Leo, A.; Taft, R. W. (Chem. Rev., 1991)

Comprehensive Organic Synthesis – Selectivity, Strategy and Efficiency in Modern Organic Chemistry - Shiosaki, K. (The Eschenmoser Coupling Reaction, 1993)

(untitled) - Hussaini, S. R.; Chamala, R. R.; Wang, Z. (Tetrahedron, 2015)

(untitled) - Huang, P.-Q.; Ou, W.; Ye, J.-L. (Org. Chem. Front., 2015)

(untitled) - Huang, P.-Q.; Ou, W. (Eur. J. Org. Chem., 2017)

(untitled) - Pal, A.; Hussaini, S. R. (ACS Omega, 2019)

(untitled) - Guillaumel, J.; Demerseman, P.; Clavel, J.-M.; Royer, R.; Platzer, N.; Brevard, C. (Tetrahedron, 1980)

(untitled) - Rokade, B. V.; Guiry, P. J. (J. Org. Chem., 2020)

(untitled) - Kumler, W. D.; Eiler, J. J. (J. Am. Chem. Soc., 1943)

(untitled) - Swain, C. G.; Scott, C. B. (J. Am. Chem. Soc., 1953)

(untitled) - Manikyamba, P.; Sundaram, E. V. (Int. J. Chem. Kinet., 1990)

(untitled) - Trost, B. M.; Hirano, K. (Org. Lett., 2012)

(untitled) - El-Faham, A.; Al Marhoon, Z.; Abdel-Megeed, A.; Albericio, F. (Molecules, 2013)

(untitled) - Chen, G.; Liu, B.; Tang, Y.; Deng, Q.; Hao, X.-j. (Heterocycl. Commun., 2010)

(untitled) - Li, C.; Go, Y.; Mao, Z.; Koyano, K.; Kai, Y.; Kanehisa, N.; Zhu, Q.; Zhou, Z.; Wu, S. (Bull. Chem. Soc. Jpn., 1996)

(untitled) - Periyaraja, S.; Mandal, A. B.; Shanmugam, P. (Org. Lett., 2011)

(untitled) - Liu, Y.-Y.; Duan, S.-W.; Zhang, R.; Liu, Y.-H.; Chen, J.-R.; Xiao, W.-J. (Org. Biomol. Chem., 2016)

(untitled) - Hassan, A. A.; El-Shaieb, K. M. A.; Abd El-Aal, A. S.; Bräse, S.; Nieger, M. (J. Heterocycl. Chem., 2016)

(untitled) - Manaka, A.; Sato, M. (Synth. Commun., 2005)

(untitled) - Bergman, J.; Pettersson, B.; Hasimbegovic, V.; Svensson, P. H. (J. Org. Chem., 2011)

(untitled) - Voß, J.; Walter, W. (Justus Liebigs Ann. Chem., 1968)